EUROPEAN UNION PROPERTY LAW: REVIEW OF THE MAIN PROVISIONS AND PECULIARITIES - Martsenko, Nataliia; Melnychuk, Anastasiia; Remenyak, Olesya (Актуальні проблеми правознавства, 2023)
European Union (EU) property law is a relatively new area of law that is developing rapidly in view of the challenges posed by time to the legislator and law enforcement practice. Today, EU property law lacks structure and a clear system, which indicates the absence of a clear policy underlying the construction of rules on property rights and other real rights. In fact, the European legislature has left the issue of property rights structure out of the proper level of attention. However, property law in the EU is also developing in the case law and legislation of the EU member states, as well as in academic circles and through private initiatives. Therefore, the vectors of development of EU property law are quite diverse and complex, often complicated by an interdisciplinary approach to understanding property and interpreting its content in law. For Ukraine, it is important to understand the peculiarities of EU property law in view of European integration processes and accelerated integration into the European trade area. In this regard, this topic is particularly relevant.The article analyzes the peculiarities of the EU law of property and the main trends which influence the directions of improvement of legal categories within the institute of property law.The author analyzes the peculiarities of legal regulation and interaction between property law and contract law, and on the basis of this study the author concludes that at present, EU property law is fragmented and lacks legal structure as compared to European contract law. The author substantiates that contract law and property law are two main branches of civil law, where contract law regulates the interaction of the parties to a contract, and property law concerns legal relations with respect to property. In practice, these branches closely interact with each other, primarily due to the fact that many contracts relate to the disposal of property.It is found that most European civil law legal orders adhere to the numerus clausus principle, but in some countries the principle of an open list of real rights (numerus apertus) is used.The author substantiates the view that the theory of property rights in science is considered through an interdisciplinary approach and analysis of its various aspects with due regard to globalization, digitalization and the environmental crisis. It is established that today the EU property law is being actively updated by improving its institutional structure and taking into account the peculiarities of ownership of various objects characterized by a specific approach to legal regulation The author argues that modernization of property rights at the EU level contributes to the convergence of property rights systems at the level of EU Member States and contributes to their improvement through, in particular, expanding the content of property ownership.